(untitled) (Revista Direitos Humanos e Democracia, 2025)
This article presents the technological transformations driven by digital platforms and their effects on the precarization of labor relations, emphasizing the urgent need to incorporate the principles of international human rights treaties into the labor law framework. Its general objective is to analyze the tensions between technological innovation and the social protection of workers linked to big techs within these platforms. The specific objectives are: (i) to map the regulatory framework and Brazilian legislative initiatives concerning work mediated by digital platforms; (ii) to assess the objective and social responsibility of platforms in the face of algorithmic subordination and automation risks; (iii) to identify regulatory guidelines that reconcile free enterprise with human dignity. The methodology is based on a bibliographic review, examination of international human rights instruments, and analysis of bills under consideration and relevant jurisprudence. It finds that, despite the quantitative gains of the digital economy, regulatory gaps and state omissions exacerbate precarization, underscoring the need for a new legal framework that strengthens platform accountability and ensures dignified working conditions in accordance with international human rights standards.